1996
DOI: 10.1080/10473289.1996.10467544
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an In Situ, On-Line Purging System for the Cone Penetrometer

Abstract: Materials that will be used to construct an in situ, on-line purging system for the cone penetrometer were evaluated. Transfer efficiencies for volatile organic compounds (VOCs) through stainless steel, nickel, aluminum, and Teflon® tubings were determined using a gas-phase mixture of VOCs containing trichloromethane, tetrachloromethane, 1,1,1- trichloroethane, tetrachloroethene, hexane, benzene, toluene, and 1,2-dimethylbenzene. The water content of the gas stream had an insignificant effect on the quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…These conditions include rough handling by truck operators, severe vertical and horizontal stresses during pushes, high humidity, high concentrations of solids (i.e., silts and fines) in most samples, and transfer of analytes through tubings that can approach Therefore, with the use of the breadboard prototype, 50 m. we initially examined materials for the QVAC, including the purging vessel, a thermostated sample gas transfer line, and groundwater inlet frit. 34 For the transfer line, we found that stainless steel (grade 304 or 316) was superior to various Teflon polymers (PFA, PTFE, FEP) as well as aluminum and nickel. Stainless steel consistently transported a range of VOCs at ambient ( ) and elevated ( ) tem-25 ЊC 110 ЊC peratures and various humidities (0 -50%) quantitatively ( ).…”
Section: Prototype Designmentioning
confidence: 97%
See 1 more Smart Citation
“…These conditions include rough handling by truck operators, severe vertical and horizontal stresses during pushes, high humidity, high concentrations of solids (i.e., silts and fines) in most samples, and transfer of analytes through tubings that can approach Therefore, with the use of the breadboard prototype, 50 m. we initially examined materials for the QVAC, including the purging vessel, a thermostated sample gas transfer line, and groundwater inlet frit. 34 For the transfer line, we found that stainless steel (grade 304 or 316) was superior to various Teflon polymers (PFA, PTFE, FEP) as well as aluminum and nickel. Stainless steel consistently transported a range of VOCs at ambient ( ) and elevated ( ) tem-25 ЊC 110 ЊC peratures and various humidities (0 -50%) quantitatively ( ).…”
Section: Prototype Designmentioning
confidence: 97%
“…In previous work, we described the results obtained from testing the probe and transfer line materials used in the QVAC system. 33,34 The development of the QVAC method, including the probe design, fabrication, laboratory testing, and initial field testing, is described herein.…”
Section: Introductionmentioning
confidence: 99%